Working out how to improve livestock feeding: The FEAST feed assessment tool - Lukuyu, Ben A.; Wassena, Fred J.; Paul, Birthe K.; Mundy, Paul; Duncan, Alan J. (International Livestock Research Institute, 2016)
The ILRI-supported MilkiT project has used the Feed Assessment Tool (FEAST) to address livestock feeding challenges and provide solutions for smallholder livestock farmers in India and Tanzania.